Regulators of Ovarian Preantral Follicle Development - McGee, Elizabeth A.; Raj, Renju S. (Seminars in Reproductive Medicine, 2015)
Preantral follicle development has become an increasingly recognized area of study in the last two decades. Factors that regulate the growth survival and differentiation of these small, yet complex structures have been identified. The field of fertility preservation and a need for increased numbers of mature oocytes for stem cell research revealed how little we knew of how follicles got from the primordial stage to the antral stage with a healthy and competent oocyte inside. This work discusses the role of gonadotropins in regulating preantral follicles and also the role of the TGF-β family members and their associated Smad signaling molecules in preantral follicle development. Preantral follicle development is a necessary step to fertility in females and further understanding of this process is essential for progress in both infertility care and the enlarging field of in vitro folliculogenesis.
Keywords: preantral follicle; ovary; Smad; FSH; TGF-β